2019
DOI: 10.3329/uhj.v15i2.42666
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Pre-Hospital Delay In Patients with Acute Myocardial Infarction

Abstract: Acute coronary syndrome is a lethal condition. Treatment modality and success mostly depend on time yielded since onset of symptoms. It is known for more than 30 years that delay between symptom onset and treatment of less than 60 min are desirable, but pre hospital delays remain unacceptably long worldwide including Bangladesh. A greater understanding of the contributing factors may help to reduce delays. A number of sociodemographic, clinical, social and proximal factors have been associated with pre hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Generally, patients’ behavioral and cognitive responses toward the symptoms of AMI have been associated with prehospital delay. Some studies have related it to prehospital delay [ 14 ], while others have found that it minimizes the delay [ 36 , 37 ]. Our study analyzed seven variables under these categories and found that two variables were related to prehospital delay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, patients’ behavioral and cognitive responses toward the symptoms of AMI have been associated with prehospital delay. Some studies have related it to prehospital delay [ 14 ], while others have found that it minimizes the delay [ 36 , 37 ]. Our study analyzed seven variables under these categories and found that two variables were related to prehospital delay.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have proven that prehospital delay is the major contributor to delayed treatment in South Asian countries such as India [ 10 , 11 ], Pakistan [ 12 , 13 ], Bangladesh [ 14 ], and Sri Lanka [ 15 ]. However, there is little or no information regarding the prehospital delay in the Maldives.…”
Section: Introductionmentioning
confidence: 99%
“…There are three main reasons for the delay: patient-related, transport and hospital-related delay. Patient-related delay refers to the time from the onset of symptoms to make the initial decision to seek medical assistance [7,8]; this depends on the patients' perception and beliefs about their disease, which was found to be more challenging than transport and hospital delays [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors contribute to the delay in seeking medical help, and previous studies found financial problems, lack of health insurance, and lack of time as the most common causes [10,11]. Furthermore, some patients hesitated because of misunderstanding the nature of their pain and other cardiacrelated symptoms [5,8,11,12]. Mistrust between the patient and the physician as a result of delayed attention from the physician and other healthcare providers was also reported [11], as were psychological problems such as anxiety and fear of the hospital and medical equipment [13].…”
Section: Introductionmentioning
confidence: 99%